Non-thermal atmospheric pressure plasma activates Wnt/β-catenin signaling in dermal papilla cells - Ji-Hye Hwang (Nature Portfolio, 2021)
Abstract There is an unmet need for novel, non-pharmacological therapeutics to treat alopecia. Recent studies have shown the potential biological benefits of non-thermal atmospheric pressure plasma (NTAPP), including wound healing, angiogenesis, and the proliferation of stem cells. We hypothesized that NTAPP might have a stimulatory effect on hair growth or regeneration. We designed an NTAPP-generating apparatus which is applicable to in vitro and in vivo experiments. The human dermal papilla (DP) cells, isolated fresh hair follicles, and mouse back skin were exposed with the NTAPP. Biological outcomes were measured using RNA-sequencing, RT-PCR, Western blots, and immunostaining. The NTAPP treatment increased the expression levels of Wnt/β-catenin pathway-related genes (AMER3, CCND1, LEF1, and LRG1) and proteins (β-catenin, p-GSK3β, and cyclin D1) in human DP cells. In contrast, inhibitors of Wnt/β-catenin signaling, endo-IWR1 and IWP2, attenuated the levels of cyclin D1, p-GSK3β, and β-catenin proteins induced by NTAPP. Furthermore, we observed that NTAPP induced the activation of β-catenin in DP cells of hair follicles and the mRNA levels of target genes of the β-catenin signaling pathway (CCND1, LEF1, and TCF4). NTAPP-treated mice exhibited markedly increased anagen induction, hair growth, and the protein levels of β-catenin, p-GSK3β, p-AKT, and cyclin D1. NTAPP stimulates hair growth via activation of the Wnt/β-catenin signaling pathway in DP cells. These findings collectively suggest that NTAPP may be a potentially safe and non-pharmacological therapeutic intervention for alopecia.